Effectiveness, Safety, and Tolerability of Esomeprazole and Domperidone in Gastroesophageal Reflux Disease - Quratulain, Sheeraz Azam, Hafiz Ali Muhammad, Waseem Javed, Omer Farooq, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study was to examine the clinical efficacy, tolerability, and safety of Esomeprazole 20 mg + sustained release (SR) Domperidone 30mg delivered once daily in adult patients for the symptomatic alleviation of dyspepsia associated with GERD. Study Design: Prospective Study Place and Duration: PIMS Hospital Islamabad. Dec 2021- May 2022 Methods: Total 97 patients of both genders had symptomatic dyspepsia associated with GERD were presented in this study. Patients were aged between 20-75 years. Informed written consent of all the patients were taken for detailed demographics. Patients were given a fixed-dose combination of Esomeprazole 20 mg and sustained-release (SR) Domperidone 30 mg once day for two weeks. Treatment efficacy was determined by whether or not patients' symptoms improved and whether or not they were happy with the care they received. Physical tests determined the level of safety and tolerability. SPSS 22.0 was used to analyze all data. Results: Among 97 patients, 56 (57.7%) patients were males and 41 (42.3%) were female patients. Mean age of the patients was 38.22±16.49 years. 52 (53.6%) patients were from urban areas and 58 (59.8%) patients were literate. Most common symptoms were heart burn, epigastric pain, acid regurgitation and belching among all cases. Post-treatment, we found significantly reduction in severity of symptoms among all cases with p value <0.002. Frequency of satisfaction rate among all cases was 91 (93.8%). Adverse events were found only in 8 (8.2%) patients. Conclusion: According to the results of this study, a combination of sustained-release (SR) domperidone 30 mg and fixed-dose esomeprazole 20 mg may be an effective and well-tolerated therapy option for the management of symptomatic relief of dyspepsia associated with GERD in adult patients. Keywords: Domperidone, Esomeprazole, Dyspepsia, GERD, Outcomes